Use of grape residue flour in lactating dairy sheep in heat stress: Effects on health, milk production and quality - Alba D.F.* (2019)
© 2019 Elsevier LtdThe objective of this study was to evaluate the effects of grape residue flour (GRF)on antioxidant activities, biochemistry variables, components of the immune system and milk production and quality of Lacaune sheep in heat stress. Twenty-seven multiparous lactating sheep [50 ± 1.8 days (d)milking]were stratified by initial body weight, age, date of lambing and milk production and assigned randomly to 1 of 3 treatments (9 sheep/treatment): no GRF supplementation (control group)or supplementation at 1% (10 g/kg GRF)or 2% (20 g/kg GRF)of GRF (bark and seed)in the concentrate (grains and minerals mixture). Each ewe received 0.8 kg/d of concentrate, 3.6 kg/d of corn silage, and 0.25 kg/d of Cynodon spp hay. Milk production along with blood and milk samples were collected on d 1, 10 and 15. The 2% GRF sheep had increased serum concentrations of superoxide dismutase and glutathione peroxidase activity on d 15 compared to control sheep. Over time (d 10 to 15), lipid peroxidation was reduced in 2% GRF sheep. Total serum antioxidant capacity was greater in 2% GRF sheep compared to control sheep on d 10 and 15. Superoxide dismutase and glutathione peroxidase activity in milk samples were greater in 2% GRF sheep compared to control sheep. Supplementation with GRF did not affect milk production but GRF sheep were more efficient compared to control sheep. Protein and lactose concentrations were similar between treatments, but total solids and fat concentrations were greater in 2% GRF sheep compared to control sheep on d 15. Somatic cell count was reduced in GRF sheep compared to control sheep. In summary, supplementation with 2% GRF in dairy sheep in heat stress resulted in antioxidant and anti-inflammatory responses, which improved milk quality and reduced somatic cell count and lipid peroxidation.